2022
DOI: 10.1111/1442-1984.12390
|View full text |Cite
|
Sign up to set email alerts
|

Effective hawkmoth pollination in the primarily bee‐pollinated Salvia daiguii—an example of adaptive generalization

Abstract: Many plants exhibit floral traits that are directed to specific pollinator groups. Nevertheless, they can also attract less‐adapted pollinators and gain benefits under certain conditions, resulting in adapted generalization. This may be the case in Salvia daiguii (Lamiaceae), an endangered, bee‐pollinated species native to the Tianmenshan National Forest Park, China. The flower appears phenotypically specialized to bees but is also visited by Macroglossum bombylans. In the present study, we test whether the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Xiao, Huang, and Wei ( 2022 ) and Xiao, Liu, et al. ( 2023 ) conducted extensive surveys in more than 25 provinces and cities during 2011–2021 and also found this species only in the vicinity of Tianmenshan National Forest Park, Zhangjiajie City, Hunan Province, China (Figure 1 ‐TNFP 2 and ZEFR 1). In the present study, although we found the largest point ZEFR 2 to date, with 274 individuals, it was still restricted to the vicinity of Tianmenshan National Forest Park.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Xiao, Huang, and Wei ( 2022 ) and Xiao, Liu, et al. ( 2023 ) conducted extensive surveys in more than 25 provinces and cities during 2011–2021 and also found this species only in the vicinity of Tianmenshan National Forest Park, Zhangjiajie City, Hunan Province, China (Figure 1 ‐TNFP 2 and ZEFR 1). In the present study, although we found the largest point ZEFR 2 to date, with 274 individuals, it was still restricted to the vicinity of Tianmenshan National Forest Park.…”
Section: Discussionmentioning
confidence: 99%
“…Salvia daiguii has four ovules per flower and produces a small amount of nectar at the base of the corolla tube. Previous studies found that Apis cerana is the primary pollinator of S. daiguii , but its curved style allows the nectar thief Macroglossum bombylan s to become a secondary pollinator (Xiao, Liu, et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations